Sistem Informasi Penjadwalan Mata Pelajaran Menggunakan Algoritma Artificial Bee Colony Berbasis Web - Imam Saepul Azmi; Ina Najiyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Course Scheduling Information System Using Web-Based Artificial Bee Colony AlgorithmOne of the educational institutions in Cicalengka District and Bandung Regency is SMK Yadika Cicalengka. has difficulties with scheduling and plotting. At SMK Yadika Cicalengka, the existing scheduling system is still done manually using Microsoft Excel. This becomes less effective because it takes quite a long time and requires an assessment of each teacher's teaching availability every day. This research aims to create a scheduling system that can optimize the time to create subject schedules and accurately divide teaching assignments. Using the artificial bee colony method, this research develops the system and achieves optimal results by imitating how bee colonies search and exploit food sources effectively. In the case of this research, iteration and solution selection will be performed to reduce the breadth of the problem. The results of this study show that the created system is more efficient in time scheduling, with an average value of 96%.